Aligning Students' Competencies with Global Workforce Standards: A Discrepancy Evaluation Model (DEM) Perspective - Tsani, Iskandar; Sufirmansyah, Sufirmansyah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines UIN Syekh Wasil Kediri undergraduates' work-related competencies through the Discrepancy Evaluation Model (DEM) lens. Recognizing that modern bachelor‐level programs are increasingly geared toward employability, this evaluative field research employs Provus' DEM framework alongside a convergent mixed‐methods design. Qualitative insights were gathered via interviews, observations, and document analyses, while quantitative data were obtained through a structured questionnaire. A total of 386 students from the PBA, IAT, and PAI programs participated. We adopted Spencer and Spencer's five‐factor competency model to establish performance standards, motives, traits, self‐concept, knowledge, and skills. The questionnaire, developed in collaboration with the Insight Yogyakarta Institute, set a benchmark of 87 points as the minimum acceptable score. The process phase measured student performance, revealing that 51.3% (n = 198) met or exceeded this threshold. Notable gaps emerged in motives (mean = 15.87) and skills (mean = 18.16), attributable to intense labor‐market competition and a curriculum that insufficiently nurtures interpersonal and technical proficiencies. This study contributes to developing recommendations in the form of targeted interventions to improve students' work competencies, namely through motivational seminars and skill development workshops for students and pedagogical development programs for lecturers. This article has implications for enriching work competency theory, curriculum development strategies, and institutional evaluation design.